2019
DOI: 10.3389/fnins.2019.00994
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Self-Construal Priming in the Ultimatum Game

Abstract: Research from cultural and social psychology has identified a central role of self-construal, or the way one views themselves in relation to others, in social cognition. Accordingly, it is plausible that self-construal plays an instrumental role in important aspects of decision-making relating to fairness considerations. Prior research has shown that priming methodology is a useful tool to experimentally isolate the effect of self-construal on social decision-making processes. In the current study we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…Previous behavioral studies found that females were more averse to inequity than males (Croson & Gneezy, 2009; García‐Gallego et al., 2012; Solnick, 2001). Evidence from neuroimaging studies further showed that females exhibited greater activations than males in the emotional (e.g., dACC) and mentalizing (e.g., vmPFC) systems in response to unfair offers even in the absence of behavioral differences (Dulebohn et al., 2016; Flinkenflogel et al., 2019; Kopsida et al., 2016). These findings suggest that the psychological and neurocognitive processes associated with costly punishment are different in females from males.…”
Section: Discussionmentioning
confidence: 99%
“…Previous behavioral studies found that females were more averse to inequity than males (Croson & Gneezy, 2009; García‐Gallego et al., 2012; Solnick, 2001). Evidence from neuroimaging studies further showed that females exhibited greater activations than males in the emotional (e.g., dACC) and mentalizing (e.g., vmPFC) systems in response to unfair offers even in the absence of behavioral differences (Dulebohn et al., 2016; Flinkenflogel et al., 2019; Kopsida et al., 2016). These findings suggest that the psychological and neurocognitive processes associated with costly punishment are different in females from males.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, cultural neuroscience has gradually emerged as the hottest research topic since 2014. At the technical level, fMRI has been widely used by scholars since 2019 (Flinkenflogel et al, 2019;Murray et al, 2020;Shkurko, 2020), culture and self have remained the focus of researchers (Russell et al, 2019;Chiao et al, 2020;Kwon et al, 2021), and adolescent has emerged as the intellectual theme in 2021 (Chen and Qu, 2021;Rapp et al, 2021). Thus, the use of fMRI technology, combined with cultural neuroscience methods to study the impact of Chinese and Western cultural differences on brain function, appeared to be the future research trend.…”
Section: Research Frontier Analysismentioning
confidence: 99%
“…Many factors, such as cultural biases and individual predispositions, influence self‐other discrimination. Many experimental paradigms, such as ultimatum game (Flinkenflogel et al, 2019; Ogawa et al, 2023) and social discounting task (Jones, 2022) have been used to investigate the factors involved in social interactions and self‐other discrimination. Thus, the neural correlates of in‐group and out‐group biases in this discrimination are convincingly demonstrated (Fallon et al, 2020; Saarinen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%